Valorant Haven Strategy Using BIP and Weighted Graph - Benna Kireyna, Ermelinda; Pratama, Jovian Dian; Rizky Pratama, Mauliddino; Dwiyeni, Sri Lutfiya; Diyanti, Apni; Rico Dewanto, Bernardinus; Sunarsih (Journal of Mathematics: Theory and Applications, 2024)
Strategy in a competitive video game is needed to reach a successful game, for example, Valorant. Route planning is one of the strategies in playing games. In consideration of making a new strategy, this research develops a binary integer programming (BIP) model to generating optimal route depending on passable paths, travel time, kills, and survivability. By using POM QM for Windows to compute the model, we obtained optimal modified routes that can be combined in the role and agent composition.